GAMBARAN FAKTOR RESIKO YANG MENYEBABKAN KEJADIAN PENYAKIT TIDAK MENULAR PADA REMAJA DI MADRASAH ALIYAH HASANAH KOTA PEKANBARU - Neni Ristiani; Abdul Karim; Mathdika Sakti (Collaborative Medical Journal, 2024)
Non-communicable diseases are a health issue that is currently of national and global concern. Non-communicable diseases (NCDs) are diseases that are not transmitted to other people through contact in any form. Currently, PTM does not only affect the elderly, but is starting to appear more frequently in young and working age groups. This is due to the rapid development of technology, environmental changes, and the transition from traditional to modern lifestyles. This study aims to provide an overview of the risk factors for NCD behavior in adolescents. This research was conducted at Madrasah Aliyah Hasanah, Pekanbaru City in September-October 2023. This research used a descriptive observational method with a cross-sectional approach on 68 respondents. The BMI results that were at risk (>25kg/m2) were 20.6%, the examination of abdominal circumference found excess abdominal circumference as much as 13.2%, blood pressure examination >140/90mmHg was 8.8% of respondent, cholesterol examination showed high cholesterol results as much as 4.4%. The research results showed that 23.5% of respondents had smoking habits, 10.3% of respondents drank alcohol, 79.4% consumed <5 portions of fruit and vegetables a day and 10.3% of respondents lacked physical activity. The results of self-examination of non-communicable diseases only found asthma in 8.8% respondent. The results of examination of the history of non-communicable diseases in the family found 11.8% diabetes mellitus, 27.9% hypertension, 7.4% heart disease, 4.4% stroke, 13.2% asthma, 1.5% cancer, and 17,6% cholesterol.